COMPARATIVE ANALYSIS OF PSYCHOLOGICAL FACTORS AND MODELS DETERMINING CONSUMER BEHAVIOR - Avanesyan, D. H. (Modern Psychology, 2019)
This article represents the analysis of the psychological factors related to consumer behavior and widely disseminated models. Interdisciplinary models describing psychological behavior include the subject and object linked with the criteria of definition, interdisciplinary situation and goals of the psychological behavior. According to the analysis psychological methodology will contribute to the scientific applied possibility of response to nowadays challenges and thorough solutions.
Keywords: consumer behavior, model, psychological factors, incentive, needs, analysis.